2020
DOI: 10.3389/fnins.2020.587986
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Gut Microbiome at the Acute Stage of Ischemic Stroke in a Pig Model

Abstract: Stroke is a major cause of death and long-term disability affecting seven million adults in the United States each year. Recently, it has been demonstrated that neurological diseases, associated pathology, and susceptibility changes correlated with changes in the gut microbiota. However, changes in the microbial community in stroke has not been well characterized. The acute stage of stroke is a critical period for assessing injury severity, therapeutic intervention, and clinical prognosis. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 79 publications
(130 reference statements)
4
34
1
Order By: Relevance
“…They defined minor stroke as NIHSS score ≤ 4. In addition, the time of enrollment may also account for the discrepancy ( Jeon et al., 2020 ). For instance, they did not define the onset time of stroke and they collected fecal samples within 48 hours of admission.…”
Section: Discussionmentioning
confidence: 99%
“…They defined minor stroke as NIHSS score ≤ 4. In addition, the time of enrollment may also account for the discrepancy ( Jeon et al., 2020 ). For instance, they did not define the onset time of stroke and they collected fecal samples within 48 hours of admission.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota from AD patients were transplanted into New mechanism of neuroinflammation in Alzheimer's disease: The activation of NLRP3 inflammasome mediated by gut microbiota Kim et al, 2020 Transfer of a healthy microbiota reduces amyloid and tau pathology in an Alzheimer's disease animal model Mezö et al, 2020 Different effects of constitutive and induced microbiota modulation on microglia in a mouse model of Alzheimer's disease Wang et al, 2020 The gut microbiota attenuate neuroinflammation in manganese exposure by inhibiting cerebral NLRP3 inflammasome Amelioration of AD pathology Bourassa et al, 2016 Butyrate, neuroepigenetics and the gut microbiome: Can a high fiber diet improve brain health? Bonfili et al, 2017 Microbiota modulation counteracts Alzheimer's disease progression influencing neuronal proteolysis and gut hormones plasma levels Bonfili et al, 2018 SLAB51 probiotic formulation activates SIRT1 pathway promoting antioxidant and neuroprotective effects in an AD mouse model Rezaeiasl et al, 2019 The effects of probiotic Lactobacillus and Bifidobacterium Strains on memory and learning behavior, long-term potentiation (LTP), and some biochemical parameters in β-amyloid-induced rat's model of Alzheimer's disease Lee et al, 2019 Suppression of gut dysbiosis by Bifidobacterium longum alleviates cognitive decline in 5XFAD transgenic and aged mice Mehrabadi and Sadr, 2020 Assessment of probiotics mixture on memory function, inflammation markers, and oxidative stress in an Alzheimer's disease model of rats Aggravation of stroke pathology Singh et al, 2016 Microbiota dysbiosis controls the neuroinflammatory response after stroke Yamashiro et al, 2017 Gut dysbiosis is associated with metabolism and systemic inflammation in patients with ischemic stroke Stanley et al, 2018 An insight into intestinal mucosal microbiota disruption after stroke Ahnstedt et al, 2020 Sex differences in T cell immune responses, gut permeability and outcome after ischemic stroke in aged mice Jeon et al, 2020 Dynamic changes in the gut microbiome at the acute stage of ischemic stroke in a pig model Xu et al, 2021 Rapid gut dysbiosis induced by stroke exacerbates brain infarction in turn Amelioration of stroke pathology Wang et al, 2011 Valproic acid attenuates blood-brain barrier disruption in a rat model of transient focal cerebral ischemia: the roles of HDAC and MMP-9 inhibition Hasan et al, 2013 Effect of HDAC inhibitors on neuroprotection and neurite outgrowth in primary rat cortical neurons following ischemic insult Kim and Chuang, 2014 HDAC inhibitors mitigate ischemia-induced oligodendrocyte damage: potential roles of oligodendrogenesis, VEGF, and anti-inflammation…”
Section: Microbiota and Alzheimer's Diseasementioning
confidence: 99%
“…CNS disorders can also act on gut microbiota composition via the gut-brain axis. Table lists corresponding references, all studies are primarily based on rodent data with the exception of reference (Yamashiro et al, 2017;Haran et al, 2019;and Jeon et al, 2020).…”
Section: Microbiota and Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The species diversity of gut microbiota was also reduced upon injury ( Singh et al., 2016 ). In another model of pig stroke, the abundance of the Proteobacteria dramatically increased after stroke, while Firmicutes and Lactobacillus decreased accordingly ( Jeon et al., 2020 ). In clinical studies, intestinal dysbiosis was consistently observed in patients with acute ischemic stroke, when comparing with healthy control group ( Xia et al., 2019 ; Xu et al., 2021 ).…”
Section: The Interplay Between Stroke and Gut Microbiotamentioning
confidence: 99%